Sequential treatment of rupture of pseudoaneurysm of hepatic artery with peritoneal patch and radiological embolization. Issue 4 (6th April 2019) - Tashkandi, A; Rhaiem, R; Adlani, I; Fossaert, V; Sommacale, D; Kianmanesh, R; Piardi, T
Abstract: Bleeding after pancreatico-duodenectomy (PD) is a serious complication with high rates of morbidity and mortality. Interventional radiology techniques' using embolization and/or stenting is the optimal management. In case of hemodynamic instability, surgical treatment is mandatory, but its mortality rate is considerable. Herein, we report the management of massive bleeding in a 52-year-old-male patient, 3 weeks after PD. The patient suffered severe hemorrhage with two cardiac arrests and surgical treatment was performed immediately after resuscitation. A defect in the distal part of the hepatic artery was repaired using a peritoneal patch. A postoperative CT scan confirmed bleeding control and the presence of a pseudoaneurysm within the patch area. The second step of the treatment was to perform selective embolization. The course was uneventful, and the patient was discharged 6 weeks later.